2020
DOI: 10.1108/ijchm-01-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Customers’ intention to use robot-serviced restaurants in Korea: relationship of coolness and MCI factors

Abstract: Purpose This study aims to empirically test a theoretical model by defining customers’ intention to use services of restaurant robots, which are rapidly developing in Korea. The proposed model incorporates three stages: coolness, motivated consumer innovativeness (MCI) and the theory of planned behaviour. Design/methodology/approach A total of 420 questionnaires were issued. The results were analysed to verify the reliability and validity of the measured variables. Structural equation modelling was used to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(184 citation statements)
references
References 62 publications
8
164
1
11
Order By: Relevance
“…Similar to the medical robots, the service robot plays the role of the shield between the tourists and employees in the catering industry. The customers’ opinion of robot-serviced restaurants was investigated in Korea [ 127 ]. Utility, attractiveness, subcultural appeal, and originality are identified as the top impactors to the motivated consumer innovativeness of the customers.…”
Section: Robots In Covid-19mentioning
confidence: 99%
“…Similar to the medical robots, the service robot plays the role of the shield between the tourists and employees in the catering industry. The customers’ opinion of robot-serviced restaurants was investigated in Korea [ 127 ]. Utility, attractiveness, subcultural appeal, and originality are identified as the top impactors to the motivated consumer innovativeness of the customers.…”
Section: Robots In Covid-19mentioning
confidence: 99%
“…For instance, Belanche et al (2020) found that customers make stronger attributions of responsibility for the service performance to human employees than to service robots, especially when service failure occurs. Moreover, in a study on the antecedents of customers' intention to use services of restaurant robots, Cha (2020) found that both hedonically and socially motivated consumer innovativeness have positive effects on customers' attitudes toward service robots.…”
Section: Literature Review On Customer Responses To Frontline Servicementioning
confidence: 99%
“…Moreover, Jörling et al (2019) found that the perceived autonomy of the robots leads to a decrease in customers' feelings of control. In restaurant settings, sensory elements of the robot service improve customer affective and attitudinal responses towards the use of robots (Cha, 2020). In hotel settings, customer intention to adopt hotel service robots is likely to be influenced by robot's level of anthropomorphism (Tussyadiah & Park, 2018).…”
Section: Literature Review On Customer Responses To Frontline Servicementioning
confidence: 99%
See 1 more Smart Citation
“…Milman et al (2020) argued that safety qualities and human orientation qualities of service robots are the core elements affecting the perceived robotic functionality of theme park visitors, regardless of their design. In case of restaurants, Cha (2020) derived that the robots’ ability to interact with their customers has more significant impact on customer’s usefulness of robots rather than the technical aspects. Among many elements of consumer innovativeness, Kim et al (2020) demonstrated that hedonic experience-seeking, quality experience-seeking, social distinctiveness and venturesomeness positively influence the overall image of the restaurant adopting robots.…”
Section: Literature Reviewmentioning
confidence: 99%